Satisfaction-driven cooperative trajectory optimisation for multi-UAV-assisted mobile edge computing. (12th May 2023) - Liu, Cuntao; Guo, Yan; Li, Ning; Yu, Weibo
This paper investigates an unmanned aerial vehicle (UAV)-assisted mobile edge computing scenario, where multiple UAVs provide computational services for user devices (UDs) with different service priorities. Taking into account UDs' different service priorities as well as diverse computation-offloading demands, a satisfaction-model is proposed, which gives consideration to UDs' satisfaction degree toward the offloading services as well as the fairness of their offloading amount. We aim to maximise UDs' sum satisfaction by jointly optimising the offloading time allocation, computing time allocation, users' transmit power, as well as UAV trajectory. A non-convex optimisation problem is formulated and an effective solution framework is proposed, where the problem is decomposed into three sub-problems that are solved alternately and iteratively by applying successive convex approximation (SCA) technique. Numerical results show that the proposed scheme achieves higher satisfaction with lower standard deviation as compared to benchmark schemes.